Evaluation of Link and Match Vocational High Schools - Industry and Bussiness World in Improving Human Resources - Amin Nurita Fajar Astuti; Samsudi Samsudi; Hadromi Hadromi (Universitas Negeri Semarang, 2021)
The government's efforts in improving the quality of human resources for Vocational High Schools graduates through the revitalization of Vocational Schools are divided into 5 managements (curriculum, human resources, cooperation, quality assurance, infrastructure). One form of cooperation is the Link and Match for Vocational High Schools - Industry and Bussiness World. The purpose of the study was to determine the evaluation of the implementation of link and match in improving the competence of Human Resources. The study was conducted using a qualitative method taking 7 Vocational High Schools in Wonosobo Regency. Data retrieval through data link and match Vocational High Schools - Industry and Bussiness World, Basic Education Data as of May 10, 2020, and open-question research data for 7 Vocational Schools. The data is processed by descriptive analysis. The results showed that the implementation of the link and match of the Vocational High School - Industry and Bussiness World that had been carried out was the implementation of industrial work practices, student competency tests and some had implemented industrial curriculum synchronization. Vocational High Schools have not succeeded in utilizing Human Resources from the expertise of industrial practitioners to the fullest. Based on the results of the study, it is recommended that there is a need for a review in the implementation of link and match of Vocational Schools-Industry and Bussiness World in improving the competence of Human Resources.